2020
DOI: 10.1002/aoc.5554
|View full text |Cite
|
Sign up to set email alerts
|

Intercalation of copper salt to montmorillonite K‐10 and its application as a reusable catalyst for Chan–Lam cross‐coupling reaction

Abstract: A simple and efficient catalytic system has been developed by adsorption of copper salt in the interlayers of montmorillonite K‐10. The catalytic system impressively exercises the green chemistry perspective leading to effortless recovery and recyclability for the cross‐coupling of arylboronic acids and N‐nucleophiles. The effect of catalytic activity was studied for electronically diverse arylboronic acids and imidazoles relying on various optimizations under optimum thermal condition. The catalytic system wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 48 publications
0
5
0
1
Order By: Relevance
“…Recently, a copper salt was intercalated into montmorillonite K10 and was characterised as a reusable catalyst up to the fourth reuse for Chan-Lam 50 cross coupling. 51 Cu( ii ) was adsorbed into the interlayers of the clay and its morphology was elucidated. The supported copper catalyst was studied for the coupling of arylboronic acid and imidazole under 1.2 : 1 ratio (Scheme 18).…”
Section: Classificationmentioning
confidence: 99%
“…Recently, a copper salt was intercalated into montmorillonite K10 and was characterised as a reusable catalyst up to the fourth reuse for Chan-Lam 50 cross coupling. 51 Cu( ii ) was adsorbed into the interlayers of the clay and its morphology was elucidated. The supported copper catalyst was studied for the coupling of arylboronic acid and imidazole under 1.2 : 1 ratio (Scheme 18).…”
Section: Classificationmentioning
confidence: 99%
“…2021 年, 贾铁争等与 Kozlowski 课题组 [48] 联合报道 图式 24 Cu-ACP-Am-Fe3O4@SiO2 催化芳基硼酸与芳香伯胺 的 C-N 偶联 Scheme 24 Cu-ACP-Am-Fe3O4@SiO2-catalyzed C-N coupling of arylboronic acids with aromatic primary amines 2020 年, Bora 等 [62]…”
Section: No-配位铜(ii)配合物催化的 Chan-lam 偶联反应unclassified
“…Beside these, the new synthetic strategies including heterogeneous catalysis, photoredox catalysis, and electrocatalysis were also employed in Chan–Lam reaction to further improve the reaction efficiency and atom economy. Specifically, various copper salts immobilized on different supports such as Wang's resin, [ 7 ] fluorapatite, [ 8 ] magnetic nanoparticles, [ 9 ] MCM‐41, [ 10 ] grapheme, [ 11 ] montmorillonite K‐10, [ 12 ] triazine‐based covalent organic frameworks (COFs), [ 13 ] metal–organic frameworks (MOFs), [ 14 ] and polyoxovanadate (POV)‐based frameworks [ 15 ] were used as highly effective and reusable heterogeneous catalysts for Chan–Lam coupling reaction of N ‐ , O‐, or S‐containing substrates with arylboronic acids. Recently, Yoo et al reported the coupling of arylboronic acids with aromatic amines catalyzed by Cu(OAc) 2 in combination with fac‐[Ir(ppy) 3 ] as photoredox catalyst, which indicated the critical role of visible‐light photocatalysis in catalytic cycles of Chan–Lam reactions and extended the scope of arylboronic acids.…”
Section: Introductionmentioning
confidence: 99%